Transpapillary biliary stenting is a risk factor for pancreatic stones in patients with autoimmune pancreatitis - Matsubayashi, Hiroyuki; Kishida, Yoshihiro; Iwai, Tomohiro; Murai, Katsuyuki; Yoshida, Masao; Imai, Kenichiro; Yamamoto, Yusuke; Kikuyama, Masataka; Ono, Hiroyuki (Endoscopy International Open, 2016)
Background and study aim: Pancreatic stones occasionally develop in autoimmune pancreatitis (AIP), often worsen endocrine and exocrine functions, and occasionally cause pain attacks. However, the risks of pancreatic stones in AIP have been poorly studied. The aim of this study was to analyze the risk factors associated with pancreatic stone formation in cases of AIP.Patients and methods: In total, 50 patients with AIP (39 males, 11 females; mean age 64.0 years), followed up for at least a year, were analyzed for their demographic and clinical findings and pancreatic stone occurrence.Results: In total, 50 patients were followed up for an average of 59.7 (12 – 120) months, with steroid treatment in 44 patients (88 %); pancreatic stones occurred in 14 (28 %) patients after the diagnosis of AIP and endoscopic treatment was needed in one patient with pain attack. The pancreatic stones appeared only in patients with long follow-up period (P < 0.001, 83.9 months vs. 49.6 months), biliary stenting (odds ratio [OR]: 8.40, P = 0.010), relapse (OR: 6.20, P = 0.023), jaundice (OR: 5.40, P = 0.019), and swelling of the duodenal major papilla (OR: 4.67, P = 0.040). Biliary stenting was placed for an average of 9.9 months in 27 patients. Multivariate analysis revealed a significant association only with biliary stenting (P = 0.011). The stones appeared relatively earlier in patients with stones in the main pancreatic duct or Santorini duct (22.1 months) than in patients where pancreatic stones developed elsewhere (53.4 months) (P = 0.018).Conclusions: The risk of pancreatic stone development should be taken into account when a biliary stent is placed in patients with AIP.